Distinct effects of dietary ALA, EPA and DHA on rat adipose oxylipins vary by depot location and sex. (February 2018) - Mendonça, Anne M.; Cayer, Lucien G.J.; Pauls, Samantha D.; Winter, Tanja; Leng, Shan; Taylor, Carla G.; Zahradka, Peter; Aukema, Harold M.
Abstract: Dietary EPA and DHA given together alter oxylipins in adipose tissue. To compare the separate effects of individual dietary n-3 PUFA on oxylipins in different adipose depots (gonadal, mesenteric, perirenal, subcutaneous) in males and females, rats were provided diets containing higher levels of α-linolenic acid (ALA), EPA or DHA. Each n-3 PUFA enhanced its respective oxylipins the most, while effects on other n-3 oxylipins varied. For example: in perirenal and subcutaneous depots, more DHA oxylipins were higher with dietary ALA than with EPA; dietary EPA uniquely decreased 14-hydroxy-docosahexaenoic acid, in contrast to increasing many other DHA oxylipins. The n-3 PUFAs also reduced oxylipins from n-6 PUFAs in order of effectiveness: DHA > EPA > ALA. Diet by sex interactions in all depots except the perirenal depot resulted in higher oxylipins in males given DHA, and higher oxylipins in females given the other diets. Diet and sex effects on oxylipins did not necessarily reflect effects on either their tissue phospholipid or neutral lipid PUFA precursors. These varying diet and sex effects on oxylipins in the different adipose sites indicate that they may have distinct effects on adipose function. Highlights: Each dietary n-3 PUFA increased its respective oxylipins the most in all adipose depots. Effects of dietary n-3 PUFA on other oxylipins varied by diet, sex and by depot. Oxylipins were higher in males on the DHA diet, but higher in females on other diets. Diet and sex effects on oxylipins did not reflect phospholipid or neutral lipid PUFA. Dietary EPA uniquely decreased 14-hydroxy-docosahexaenoic acid.